Psychological mechanisms for enhancing creativity in future music teachers - Rajabov Azamat Sharifovich (Psychohealth: Scientific Journal of Psychology and Mental Health, 2025)
Purpose: This study aims to explore the psychological mechanisms that foster creativity among future music teachers. It particularly examines how emotional intelligence, cognitive flexibility, self-efficacy, and intrinsic motivation interact to enhance creative potential during teacher preparation programs. Research methodology: A mixed-method approach was employed, combining quantitative surveys and qualitative interviews with 120 music education students from three universities. Standardized instruments measured emotional intelligence, self-efficacy, and cognitive flexibility, while semi-structured interviews captured students’ perceptions of creativity development in pedagogical contexts. Data were analyzed using multiple regression and thematic coding to identify significant predictors and underlying psychological processes. Results: Findings reveal that emotional intelligence and intrinsic motivation are the strongest predictors of creative engagement, while cognitive flexibility mediates the relationship between self-efficacy and creative outcomes. Students who received reflective and autonomy-supportive instruction reported higher creative performance and stronger intrinsic drive. Conclusions: Creativity in future music teachers is deeply rooted in emotional and cognitive mechanisms that can be intentionally developed through psychologically informed teacher training. Enhancing emotional regulation, adaptive thinking, and motivation can significantly elevate creative pedagogical practices. Limitations: The study is limited to pre-service music teachers and does not account for cross-cultural variations or longitudinal effects of creativity development. Contribution: This research contributes to music pedagogy by providing an integrative psychological framework for cultivating creativity in teacher education and suggesting practical interventions for curriculum design.